Development and optimization of a novel nanocarrier SabiWhite-loaded ethosomal gel for targeted skin inflammation complicated by multidrug-resistant pathogens - Shi, Gaofeng; Guo, Yun; Yang, Minlie (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to develop and evaluate SabiWhite-loaded ethosomes (SW-ETH) for topical application, focusing on improving stability, biocompatibility, and therapeutic efficacy. Ethosomal formulations are known for their enhanced drug delivery properties, making them suitable for skin inflammation.MethodsThe SW-ETH formulations were developed utilizing an adapted cold preparation technique. A 3² factorial design was used to optimize phospholipid concentration and ethanol content, and their impact on vesicle size and entrapment efficiency (EE%) was assessed. Structural characterization of SabiWhite was performed using melting point determination, Fourier-Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD). In vitro drug release was assessed using a Franz diffusion cell, and anti-inflammatory and skin irritation studies were performed on Wistar rats.ResultsSabiWhite exhibited a melting point of 96°C and characteristic FTIR peaks, confirming its identity and purity. XRD analysis revealed its crystalline nature, while ethosomal formulations showed a shift to an amorphous state. The optimized SW-ETH formulation (SW-ETH 6) had a vesicle size of 184.4 nm, an EE% of 92.5%, and a zeta potential of -13.50 mV, indicating stable and uniform vesicles. In-vitro drug release from SW-ETH 6 showed a sustained release profile with 93.12% drug release over 24 hours. In vivo, SW-ETH demonstrated significant anti-inflammatory effects with 36.17% edema inhibition at 150 minutes, comparable to Diclofenac gel (41.92%). No skin irritation was observed, and the formulation was classified as non-irritant. Stability tests confirmed minimal changes in appearance, viscosity, and drug content over 120 days at different storage conditions.ConclusionSW-ETH demonstrated effective drug encapsulation, enhanced anti-inflammatory activity, and excellent biocompatibility, making it a promising candidate for topical therapy. Further clinical validation is warranted to confirm its therapeutic potential.